The clinical significance of small copy number variants in neurodevelopmental disorders. Issue 10 (8th August 2014) - Asadollahi, Reza; Oneda, Beatrice; Joset, Pascal; Azzarello-Burri, Silvia; Bartholdi, Deborah; Steindl, Katharina; Vincent, Marie; Cobilanschi, Joana; Sticht, Heinrich; Baldinger, Rosa; Reissmann, Regina; Sudholt, Irene; et al.
Abstract : Background: Despite abundant evidence for pathogenicity of large copy number variants (CNVs) in neurodevelopmental disorders (NDDs), the individual significance of genome-wide rare CNVs <500 kb has not been well elucidated in a clinical context. Methods: By high-resolution chromosomal microarray analysis, we investigated the clinical significance of all rare non-polymorphic exonic CNVs sizing 1–500 kb in a cohort of 714 patients with undiagnosed NDDs. Results: We detected 96 rare CNVs <500 kb affecting coding regions, of which 58 (60.4%) were confirmed. 6 of 14 confirmed de novo, one of two homozygous and four heterozygous inherited CNVs affected the known microdeletion regions 17q21.31, 16p11.2 and 2p21 or OMIM morbid genes ( CASK, CREBBP, PAFAH1B1, SATB2; AUTS2, NRXN3, GRM8 ). Two further de novo CNVs affecting single genes ( MED13L, CTNND2 ) were instrumental in delineating novel recurrent conditions. For the first time, we here report exonic deletions of CTNND2 causing low normal IQ with learning difficulties with or without autism spectrum disorder. Additionally, we discovered a homozygous out-of-frame deletion of ACOT7 associated with features comparable to the published mouse model. In total, 24.1% of the confirmed small CNVs were categorised as pathogenic or likely pathogenic (median size 130 kb), 17.2% as likely benign, 3.4% represented incidental findings and 55.2% remained unclear. Conclusions: These results verify the diagnostic relevance of genome-wide rare CNVs <500 kb, which were found pathogenic in ∼2% (14/714) of cases (1.1% de novo, 0.3% homozygous, 0.6% inherited) and highlight their inherent potential for discovery of new conditions.